Estimation of 1-day extreme rainfall by Hershfield Method for Klang River basin in Malaysia. - Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Kabbashi, Nassereldeen Ahmed; Shaaban, Ahmad Jamaluddin; Ghazali, Abdul Halim (International Journal Organization, 2010)
It is very important for the hydrologists, water resources engineers and relevant authorities to use the local data and be as accurate as possible in calculating the probable maximum flood (PMF) which, in turn, is strongly related to the extreme rainfall amount commonly known as probable maximum precipitation (PMP). The main objective of designing spillways using the PMF is to avoid the overtopping of dams as a result of very high rainfall. If the estimations are not correct the structures would be either under designed (which may have very severe consequences on the downstream areas) or over designed resulting in extra cost of the project. In Malaysia, the estimation of design floods in the past was done on the basis of frequency analysis, regional flood envelopes, historical flood marks, empirical equations and engineering judgement. Most of these estimations were based on transposition of data from foreign nations. This study took initiative to develop local statistical parameters for the quick estimation of PMP in the State of Selangor, which is the most important region of the country. Sixty-nine (69) rainfall stations were selected based on the quantity and quality of the data available. Hershfield method was applied on the local rainfall data to determine the most important parameter of the statistical model (Km), which varied within 5.5 and 13.7. The newly calculated daily PMP values (24-hour duration) were 2 to 3 times higher than the mean maximum rainfall values. The new method found to be more realistic with respect to the local rainfall pattern